Implications of changes in amplitude and contour of the mercury strain gauge plethysmograph pulse tracing. Issue 8 (August 1978) - Chandraratna, P A; San Pedro, S; Schneider, R; Abrams, D; Langevin, J
Abstract : Alterations in the mercury strain gauge plethysmograph pulse tracing have been previously thought to denote changes in venous tone. This study was designed to define the implications of changes in amplitude and contour of pulse tracing. Seven normal subjects were studied. After control measurements, amyl nitrite was administered and the pulse tracing was recorded. When the haemodynamic state had returned to control levels 0.4 mg sublingual glyceryl trinitrate (GTN) was given. The amplitude of the plethysmograph pulse tracing (Y mm) and the vertical distance from the dicrotic notch to the peak of the pulse tracing (X mm) were measured. With amyl nitrite, the amplitude of the pulse tracing (Y) decreased from 10.4 +/- 1 to 4.5 +/- 0.6 mm (mean +/- SEM), while the X/Y ratio increased from 0.7 +/- 0.02 to 0.98 +/- 0.02 (P less than 0.005). After GTN Y increased from 9.3 +/- 0.8 to 31 +/- 4.8 mm (P less than 0.005) and X/Y ratio increased from 0.7 +/- 0.06 to 0.99 +/- 0.01 (P less than 0.005). Since it is known that amyl nitrite produces venoconstriction and arteriolar dilatation, and GTN causes venous and arteriolar dilatation, we conclude that an increase in Y reflects venous dilatation, and an increase in X/Y ratio, that is a fall in the dicrotic notch, denotes arteriolar dilatation. Thus, the plethysmograph pulse tracing can be used to assess the effects of drugs on the capacitance and resistance beds.